2016
DOI: 10.1021/acsami.5b11639
|View full text |Cite
|
Sign up to set email alerts
|

Interfaces with Tunable Mechanical and Radiosensitizing Properties

Abstract: We report the fabrication of a composite containing nanostructured GaOOH and Matrigel with tunable radiosensitizing and stiffness properties. Composite characterization was done with microscopy and rheology. The utility of the interface was tested in vitro using fibroblasts. Cell viability and reactive oxygen species assays quantified the effects of radiation dosages and GaOOH concentrations. Fibroblasts' viability decreased with increasing concentration of GaOOH and composite stiffness. During ionizing radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…AB & ROS Cellular Assays : The cell viability and ROS assays in the presence of the semiconductor samples were done based on Berg et al Cell viability was assessed using the Alamar Blue assay. In addition to day 0, AB was measured at days 1, 3, and 5.…”
Section: Methodsmentioning
confidence: 99%
“…AB & ROS Cellular Assays : The cell viability and ROS assays in the presence of the semiconductor samples were done based on Berg et al Cell viability was assessed using the Alamar Blue assay. In addition to day 0, AB was measured at days 1, 3, and 5.…”
Section: Methodsmentioning
confidence: 99%
“…33 GaOOH/Matrigel composites have been used to modulate the behavior of cells on surfaces with variable stiffness containing a radiosensitizing material. 34 Such studies allow one to understand how to enhance the biological response on a matrix with variable stiffness under therapeutically relevant conditions such as X-ray radiation. Gallium compounds have shown photocatalytic activity, bioavailability and Ga 3+ ions are antiproliferative to pathologically proliferating cells such as cancer cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The possibility of surface functionalization with a short-lived radiotracer such as 68 Ga may also allow for positron emission tomography of cancer cells . GaOOH/Matrigel composites have been used to modulate the behavior of cells on surfaces with variable stiffness containing a radiosensitizing material . Such studies allow one to understand how to enhance the biological response on a matrix with variable stiffness under therapeutically relevant conditions such as X-ray radiation.…”
Section: Introductionmentioning
confidence: 99%
“…We note that in prior work we have also assessed the Ga toxicity using an extremely water-soluble salt: Ga(NO 3 ) 3 . 18 Previously, we recorded no concentration dependence on toxicity. In this work, we test the effects of the collective behavior hypothesized to contribute to the production of more ROS and result in an enhanced radiosensitization.…”
Section: Introductionmentioning
confidence: 95%
“…The current work builds on prior promising results that demonstrated that the presence of a scintillator material inside a scaffold triggered different cellular responses when radiation was used. 17 , 18 These studies performed by Berg et al have demonstrated the behavior of GaOOH nanoparticles in cell free environments of both water and cell growth media. We now study the effect of GaOOH particle anisotropy in a composite.…”
Section: Introductionmentioning
confidence: 99%